PENGARUH TAX AMNESTY, TAX JUSTICE, TAX MORALE, TERHADAP TAX COMPLIANCE DENGAN TINGKAT KEPUASAN SEBAGAI VARIABEL INTERVENING - Daryatno, Andreas Bambang (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract - The 2022 tax revenue target has indeed been met, even exceeding the target set by the ministry of finance. Realization of tax revenue reached IDR 2,034.5 trillion or 114% of the Presidential Decree 98/2022 target of IDR 1,784 trillion, growing 31.4% from the 2021 realization of IDR 1,547.8 trillion. Is this target achieved because taxpayer compliance is increasing in Indonesia! When we examine it more deeply, where the tax target is met is due to the increase in world commodity prices which boost tax revenues and downstream mining materials such as nickel and others. The purpose of this research is to obtain empirical evidence regarding the effect of tax amnesty, tax justice, tax morale on tax compliance through the level of taxpayer satisfaction as mediation. By distributing questionnaires to 120 taxpayers, a sample was chosen using the purposive sampling approach and primary data. The Smart PLS 3.0 program assists with this data processing. The results of the study are as follows Tax Amnesty (X1) has a positive and significant effect on the level of satisfaction (Z), Tax Amnesty (X1) has a positive but not significant effect on Tax Compliance (Y), Tax Justice (X2) has a positive but not significant effect on Level of Satisfaction (Z), Tax Justice (X2) has a positive and significant effect on Tax Compliance (Y), Tax Morale (X3) has a positive but not significant effect on the level of service satisfaction (Z), Tax Morale (X3) has a positive effect but not significantly to tax compliance (Y), level of service satisfaction (Z) has a positive and significant effect on tax compliance (Y), Tax Amnesty (X1), tax Justice (X2), Tax Morale (X3) indirectly, does not significantly affect Tax Compliance (Y), through the level of service satisfaction (Z). From the empirical results above, it shows that taxpayer compliance is obtained from actions to increase tax justice and the level of service satisfaction, meaning that justice and the level of satisfaction felt by taxpayers in paying taxes will make tax evasion actions always avoidable. They consciously and voluntarily pay taxes because taxes are imposed fairly and it is easy to pay taxes. Meanwhile, the tax amnesty and tax morale programs, even after being moderated by the level of service satisfaction, although they have a positive effect, still cannot increase tax compliance. This might happen due to the impact of the Covid 19 pandemic which has made a mess in the world of business or the economy, so that taxpayers are again carrying out tax evasion. Keywords: Tax Amnesty; Tax Justice; Tax Morale; Tax Compliance; Level of Satisfaction